STUDENTS’ STRATEGIES FOR REDUCING ANXIETY IN SPEAKING ENGLISH AT MADRASAH ALIYAH NURUL JIHAD TEMBILAHAN HULU - Intan Nuraini; Samsul Amri; Maizarah (Program Studi Pendidikan Bahasa Inggris, 2024)
Anxiety is a common problem that students feel when speaking English in front of the class, therefore every student who feels anxious must have a strategy to reduce anxiety in speaking so that they are able to speak English well in class. The purpose of this research is to find out what strategies students use to reduce anxiety in speaking English at MA Nurul Jihad Tembilahan Hulu based on Kondo & Ling's (2004) strategies, namely preparation, relaxation, positive thinking, peer seeking and resignation strategy. The sample for this study was the entire population of MA Nurul Jihad students consisting of 3 classes, namely class X, XI and XII, which consisted of 30 students which were taken using saturation sampling technique. This research method is a quantitative descriptive method. The results showed that students at Madrasah Aliyah Nurul Jihad Tembilahan Hulu applied five strategies to reduce their anxiety in speaking English. Students mostly applied Relaxation strategies to reduce their anxiety in speaking English. The percentage of relaxation was 81%. The second strategy was preparation there were 75%. The third strategy was positive thinking, there were 74%. The fourth strategy was peer seeking, there were 66%. And the lowest strategy was resignation, there were 46%. Based on this analysis, it can be concluded that students at Madrasah Aliyah Nurul Jihad use more relaxation strategies to reduce anxiety in speaking English, with a percentage of 81% included in the very high category or the most widely used. That means relaxation strategies can help Madrasah Aliyah Nurul Tembilahan Hulu students to reduce anxiety in speaking English.